What Does a 12 Euro Minimum Wage Mean for the Labour Market? - ZG Überblick (Wirtschaftsdienst)
Abstract The introduction of the minimum wage on 1 January 2015 was preceded by a lively debate on collective bargaining autonomy and employment effects. In an expost analysis, it appears that the negative employment effects have essentially failed to materialise. Now the German “traffic light” coalition government has decided on an increase of the minimum wage of 12 euros. The question now is whether this significant increase will set the minimum wage at a level that entails socio-political risks and will lead to job losses in the low-wage sector.